Is Training a Precondition for Enhancing Innovation Capacity? Current Perception of Employment Agencies’ Civil Servants in Romania - Alina Georgiana Profiroiu; Constantin Marius Profiroiu; Mihaela Pacesila; Ovidiu Alexandru Mihalcea (Transylvanian Review of Administrative Sciences, 2019)
The civil servants’ training process plays a key role in developing the public employees’ skills and broadening their vision. The present paper seeks to examine the perception of Employment Agencies’ civil servants regarding the effectiveness of training programs, measured through their impact on the number of projects initiated and implemented under Sectorial Operational Programme for Human Resources Development 2007-2013. The role of training programs in enhancing civil servants’ innovation capacity is also investigated. The methodology consists in an analysis of 253 projects financed by the European Social Fund (ESF) during 2009-2015 and an empirical research using a representative sample of 337 civil servants who attended EU funded training courses in project management. The conclusions of this paper indicated a direct relation between the number of projects developing training courses in ‘project management’ and the number of projects initiated and implemented annually by the territorial Agencies for Employment. Moreover, a positive correlation between the training programs and the innovation capacity of civil servants from County Agencies for Employment was also identified.